2022
DOI: 10.1155/2022/4291477
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi for Overweight/Obese Adolescents and Young Women with Polycystic Ovary Syndrome: A Randomized Controlled Pilot Trial

Abstract: Background. Exercise is one of the recommended interventions for polycystic ovary syndrome (PCOS), and current evidence has shown that Tai chi may have favorable effects. The objective of this randomized controlled pilot trial was to study the feasibility and potential effects of Tai chi for overweight/obese adolescents and young women with PCOS, so a future definitive randomized controlled trial (RCT) can be well designed and implemented. Materials and Methods. This study recruited 50 patients who were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 60 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…Table 1 lists the characteristics of each of the included studies, which were published between 2009 and 2022. Five studies were conducted in China [ 29 , 30 , 32 , 34 , 36 ] ; 2 in USA [ 31 , 35 ] ; 1 in France [ 33 ] ; 1 in Australia. [ 28 ] The TCE program was used to treat overweight or obese participants in all experimental groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 lists the characteristics of each of the included studies, which were published between 2009 and 2022. Five studies were conducted in China [ 29 , 30 , 32 , 34 , 36 ] ; 2 in USA [ 31 , 35 ] ; 1 in France [ 33 ] ; 1 in Australia. [ 28 ] The TCE program was used to treat overweight or obese participants in all experimental groups.…”
Section: Resultsmentioning
confidence: 99%
“…4), the pooled data demonstrated that TCE resulted produced large and significant improvements in LDL ( g = 2.08, 95% CI = 1.80–2.37, P = .000, I 2 = 98%) when compared to the control group. Pooled analyses from 7 parallel trials [28–32,34,36] revealed that the TG exerted a moderate and significant increase in effect size ( g = 0.69, 95% CI = 0.56–0.81, P = .000, I 2 = 96%) compared with the control group. Moreover, the pooled data demonstrated that TCE resulted produced small and significant improvements in TC ( g = 0.37, 95% CI = 0.19–0.54, P = .000, I 2 = 77%) and HDL ( g = −0.71, 95% CI = −0.86 to 0.57, P = .000, I 2 = 99%) when compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations